Pertimbangan dalam Merancang Kurikulum Strata 1 Akuntansi sebuah Pandangan - Se Tin . (Jurnal Akuntansi, 2007)
This paper intends to give some inputs and judgments to design curriculum for accounting program: First, the issues of accounting graduates; Seconds, the curriculum of accounting framework; Third, up date accounting subjects.Keywords: accounting curriculum